Patients with triangular fibrocartilage complex injuries and distal radioulnar joint instability have reduced rotational torque in the forearm. (September 2016) - Andersson, J. K.; Axelsson, P.; Strömberg, J.; Karlsson, J.; Fridén, J.
A total of 20 patients scheduled for wrist arthroscopy, all with clinical signs of rupture to the triangular fibrocartilage complex and distal radioulnar joint instability, were tested pre-operatively by an independent observer for strength of forearm rotation. During surgery, the intra-articular pathology was documented by photography and also subsequently individually analysed by another independent hand surgeon. Arthroscopy revealed a type 1-B injury to the triangular fibrocartilage complex in 18 of 20 patients. Inter-rater reliability between the operating surgeon and the independent reviewer showed absolute agreement in all but one patient (95%) in terms of the injury to the triangular fibrocartilage complex and its classification. The average pre-operative torque strength was 71% of the strength of the non-injured contralateral side in pronation and supination. Distal radioulnar joint instability with an arthroscopically verified injury to the triangular fibrocartilage complex is associated with a significant loss of both pronation and supination torque. Level of evidence: Case series, Level IV.